Dibenzo-α-pyrones from the endophytic fungus Alternaria sp. Samif01: isolation, structure elucidation, and their antibacterial and antioxidant activities. Issue 4 (16th February 2017) - Tian, Jin; Fu, Linyun; Zhang, Zihao; Dong, Xuejiao; Xu, Dan; Mao, Ziling; Liu, Yang; Lai, Daowan; Zhou, Ligang
Abstract: The EtOAc extract of the liquid fermentation of Alternaria sp. Samif01, an endophytic fungus obtained from Salvia miltiorrhiza Bunge, showed antibacterial activity against several tested bacterial pathogens. Fractionation of this extract led to the isolation of seven dibenzo-α-pyrones (1 –7 ), including one new compound, 2-acetoxy-2- epi -altenuene (1 ) and one new natural product, 3- epi -dihydroaltenuene A (2 ). The structures of the new metabolites were elucidated by comprehensive analysis of the spectroscopic data including (1D, 2D) NMR and HRESIMS, while the absolute configuration of1 was determined by TDDFT–ECD computation. Altenuisol (5 ), 4-hydroxyalternariol-9-methyl ether (6 ), and alternariol (7 ) showed inhibitory activities against the tested bacteria with minimum inhibitory concentration values in the range of 86.7–364.7 μM. A preliminary structure–antibacterial activity relationship was discussed. In addition, compounds2, 5 and6 displayed promising antioxidant effects using DPPH and hydroxyl radical assays. The cytotoxicity of the isolated compounds was evaluated as well. Abstract : The endophytic fungus Alternaria sp. Samif01 isolated from Salvia miltiorrhiza Bunge produced seven bioactive dibenzo-α-pyrones, including one new compound (1 ), whose absolute configuration was determined by ECD calculation.